If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 7)(x + 3) = 0 Reorder the terms: (7 + x)(x + 3) = 0 Reorder the terms: (7 + x)(3 + x) = 0 Multiply (7 + x) * (3 + x) (7(3 + x) + x(3 + x)) = 0 ((3 * 7 + x * 7) + x(3 + x)) = 0 ((21 + 7x) + x(3 + x)) = 0 (21 + 7x + (3 * x + x * x)) = 0 (21 + 7x + (3x + x2)) = 0 Combine like terms: 7x + 3x = 10x (21 + 10x + x2) = 0 Solving 21 + 10x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (7 + x)(3 + x) = 0Subproblem 1
Set the factor '(7 + x)' equal to zero and attempt to solve: Simplifying 7 + x = 0 Solving 7 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + x = 0 + -7 x = 0 + -7 Combine like terms: 0 + -7 = -7 x = -7 Simplifying x = -7Subproblem 2
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Solution
x = {-7, -3}
| y=31292e(-0.2x) | | y=31292e-(9) | | (x+7)-(x+3)= | | 180=(180-(2x+60))+(3x+10)+x | | y=31292e-(0.2x) | | 180=(-180+(2x+60))+(3x+10)+x | | (x+7)+(x+3)= | | 180=(-180+2x+60)+(3x+10)+x | | 180=2x+3x+-180+60+10 | | 5(x-2)+4(x+2)=14-4x | | 4+-9x=9x+-2 | | 6=3sqrt | | 8x=-4x+-3x | | -16(t^2+4t+5)=0 | | d=1/16*8^2 | | d=1/16*7^2 | | d=1/16*9^2 | | d=1/16*60^2 | | d=1/16*20^2 | | 180=78+y+1.5y | | -1(4+x)=14 | | 7(x-2)+2(x+1)=1-3x | | 11x-2y=18 | | (12x+3x+2)-(12x+5)=6x+11 | | 2(3*5)=6y | | x-3x+2x=-310 | | 2x^6-9x^5+10x^4-3x^3+10x^2+2=0 | | 7x+35=77 | | (8x*2+5x+4)-(8x*2+5)=8x+10 | | 180=-10-120+x-3x+2x | | (5x*2+6x-1)-(5x*2+8)=15 | | 310=-2x+2x |